Rechargeable Li-ion batteries with halogen-intercalated graphite electrodes
A lithium ion battery with a composite cathode and phase-separated electrolyte achieves high capacity and energy density by stabilizing anion redox reactions within the graphite lattice, addressing structural instability and cycle life issues in current lithium-ion batteries.
Patent Information
- Application Number
- JP2021552631
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-06
- Filing Date
- 2020-03-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-03-06
AI Technical Summary
Current lithium-ion batteries face limitations in achieving high energy densities due to the low capacity and poor electrical conductivity of anion redox materials, leading to structural instability and low cycle life, with suitable intercalation hosts and electrolytes yet to be identified for stable anion redox reactions.
A rechargeable lithium ion battery utilizing a composite cathode with lithium halide salts intercalated into graphite, combined with a phase-separated water-in-salt electrolyte, enabling high potential and capacity through anion redox reactions stabilized within the graphite lattice.
The battery achieves a capacity of at least 250 mAh/g and an energy density of 460 Wh/kg, with a cycle life of over 150 cycles at 99% coulombic efficiency, leveraging halogen conversion intercalation chemistry for stable anion redox reactions.
Smart Images

Figure 0007599221000008 
Figure 0007599221000009 
Figure 0007599221000010
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 814,618, filed March 6, 2019, which is incorporated by reference in its entirety.
[0002] [STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT] This invention was made with Government support under DEAR0000389 awarded by the Department of Energy, Advanced Research Projects Agency-Energy. The United States Government has certain rights in this invention.
[0003] The present invention relates to a rechargeable lithium-ion battery that includes a lithium salt-graphite composite electrode, in particular to a "water-in-salt" rechargeable lithium-ion battery having a high potential, in which at least a portion of the lithium salt is phase separated from the aqueous electrolyte. [Background technology]
[0004] Lithium-ion batteries are a convenient and powerful energy storage option. Their applications are expanding into a variety of products, including but not limited to portable electronic devices (e.g., computers, cell phones, speakers, etc.) to hybrid and electric vehicles. Lithium-ion batteries require less maintenance and exhibit higher charge storage density and voltage due to the ability to densely pack small lithium ions into the anode material, making them superior to typical lead-acid batteries.
[0005] Recent advances in aqueous electrolytes using the "water-in-salt" method have significantly extended the electrochemical potential of lithium-ion batteries to the range of 3.0 V to 4.0 V, making it possible to combine high-voltage cathodes with low-potential graphite anodes. However, the limited gravimetric capacity of intercalation cathodes based on lithium transition metal oxides (<200 mAh / g) represents a fundamental barrier to achieving higher energy densities.
[0006] The current state-of-the-art chemical structure of the intercalation cathode used in Li-ion batteries (LIBs) is Li + In its lattice, it stores electrical energy by accommodating Li and replenishes the charge from the cationic redox reactions of transition metals (Ni, Co, Mn, Fe, etc.). This occurs with good reversibility (long cycle life), but the inserted Li + They have a high molar mass per unit area and may be structurally unstable during over-delithiation, resulting in mediocre capacity (200 mAh g -1 On the other hand, anion redox reactions (O / O 2- , S / S 2- (e.g., anionic redox materials) promise much higher capacity by following a conversion reaction mechanism, but usually proceed with very low reversibility due to repeated structure destruction and reformation and the associated large volume changes during each charge-discharge cycle. The problem is further exacerbated by the low electrical and ionic conductivity of these anionic redox materials.
[0007] The combination of both cationic and anionic redox mechanisms in an intercalation host has been recently discovered in Li-rich transition metal oxide materials, where the oxygen layers participate in the cell reactions and contribute significantly to the overall capacity of the transition metal oxide. Lithium batteries based on anionic redox reactions occurring in an intercalation host are considered very attractive, since they inherit both the high energy of the anionic redox conversion reactions and the excellent reversibility from the topotactic mechanism of intercalation. PF in the electrolyte of "dual-ion" batteries6 - Anion, BF 4 - Anion, TFSI - Anions can be reversibly intercalated into graphite. However, these redox reactions occur only on the graphite lattice, rather than in the anions themselves, which is why capacities of up to 120 mAh g -1 The S / Sn ratio in porous carbon is limited to less than 2- and Br - / Br 3 - Although the redox of the cathode electrolyte is highly reversible, these anions are only physically trapped / adsorbed in the porous carbon, leading to high self-discharge and low cycle life due to undesired shuttle reactions. Ideally, to avoid shuttle reactions, the anion cathode electrolyte should phase separate from the electrolyte while stabilizing the oxidized anions by intercalation into a solid host. However, so far, suitable anions, intercalation hosts, and electrolytes have not been identified to support this ideal energy storage mechanism with sufficient capacity at high potentials. Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, there is a need for suitable intercalation hosts and electrolytes that provide higher capacity and / or higher potential. [Means for solving the problem]
[0009] In some aspects of the invention, a rechargeable lithium battery with high potential and / or high capacity is provided by utilizing halogen exchange intercalation chemistry in graphite. In one particular aspect of the invention, a rechargeable lithium ion battery (i.e., lithium battery) is provided. The lithium battery includes (i) a composite cathode including a lithium salt and graphite, (ii) an electrolyte, and (iii) an anode. In one particular embodiment, the composite cathode is configured such that an oxidation product of the lithium salt is intercalated or intercalated into the graphite. In yet another embodiment, the lithium ion battery has a capacity of greater than 200 mAh / g, typically at least about 230 mAh / g, often at least about 240 mAh / g, and in most cases at least about 250 mAh / g. In yet another embodiment, the energy density of the lithium ion battery is at least about 400 Wh / kg, typically at least about 430 Wh / kg, often at least about 460 Wh / kg, and in most cases at least about 500 Wh / kg. When referring to a numerical value, the terms "about" or "approximately" are used interchangeably herein and refer to being within an acceptable error range of the particular value as determined by one of ordinary skill in the art. The determination of such a value will depend at least in part on how the value is measured or determined, e.g., the limitations of the measurement system, i.e., the degree of precision required for a particular purpose. For example, the term "about" may mean within one standard deviation or more than one standard deviation, in accordance with the practice in the art. Alternatively, when referring to a numerical value, the term "about" may mean ±20%, typically ±10%, often ±5%, and in most cases ±1% of that numerical value. However, in general, when a particular value is described in this application and claims, unless otherwise specified, the term "about" means being within an acceptable error range of the particular value, typically within one standard deviation.
[0010] In another embodiment, the coulombic efficiency of the lithium battery is at least about 95%, typically at least about 98%, often at least about 99%, and most often at least about 99.9%.
[0011] In yet another embodiment, the lithium ion battery has a capacitance of at least about 4 V (Li / Li + ) typically has a potential of at least about 4.1 V, often at least about 4.15 V, and most often at least about 4.2 V.
[0012] In some embodiments, the composite cathode comprises multiple lithium salts, such as lithium halide salts. In yet other embodiments, the composite cathode comprises lithium chloride, lithium bromide, lithium iodide, lithium fluoride, and other halide salts, or combinations thereof. In one particular embodiment, the composite cathode comprises a combination of lithium chloride and lithium bromide.
[0013] In one particular embodiment, the electrolyte comprises a fluoride-based electrolyte. Exemplary fluoride-based electrolytes that may be used in the lithium batteries of the present invention include, but are not limited to, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluoro(oxalato)borate (LiDFOB), lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium nitrate (LiNO 3 ) or an electrolyte capable of phase separation from a lithium halide electrolyte, and mixtures thereof.
[0014] In another embodiment, the electrolyte is a water-in-bisalt electrolyte (WiBS), a high concentration organic electrolyte, an all-solid-state Condition The electrolyte may include a ceramic electrolyte, a lithium halide salt electrolyte and a phase-separable electrolyte, or a combination thereof.
[0015] Exemplary high concentration organic electrolytes include, but are not limited to, 2m lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) + 2 lithium difluoro(oxalato)borate (LiDFOB) in dimethoxyethane, 4m lithium tetrafluoroborate (LiBF) in ethylene carbonate (EC), 4 ), 7m lithium bis(fluorosulfonyl)imide (LiFSI) in fluoroethylene carbonate (FEC), and 2m lithium tetrafluoroborate (LiBF) in a 1:1 volumetric mixture of ethylene carbonate (EC) and propylene carbonate (PC). 4 ) are mentioned.
[0016] Exemplary All-Solid Condition Ceramic electrolytes include, but are not limited to, Li 4 (BH 4 ) 3 I, Li 4 (BH 4 ) 3 Br, Li 4 (BH 4 ) 3 Cl, LiBH 4 -LiBr-LiCl solid solution, Li 2 Al 2 SiP 2 TiO 13 (LASPT), Li 7 La 3 Zr 2 O 12 (LLZO), and PEO-LiTFSI polyelectrolytes.
[0017] In yet another embodiment, the electrolyte is in the form of a water-based gel. In yet another embodiment, the electrolyte further comprises poly(ethylene oxide), polyvinyl alcohol, polyacrylonitrile, poly(methyl methacrylate), polyacrylic acid, polytetrahydrofuran, polyethylene glycol dimethacrylate, poly(ethylene glycol) diacrylate, 2-hydroxyethyl acrylate, poly(ethylene glycol) methyl ether, bisphenol A ethoxylate dimethacrylate, polyvinylpyrrolidone, and other hydrophilic polymers, or combinations thereof.
[0018] In another aspect of the invention, there is provided a method of making a lithium salt-graphite composite cathode for use in a rechargeable lithium ion battery, in which in some embodiments a lithium salt is intercalated within the graphite, the method including compressing a mixture of the lithium salt-graphite composite and a polymer under conditions sufficient to produce a lithium salt-graphite composite cathode, thereby oxidizing the lithium salt and intercalating an oxidation product of the lithium salt within the graphite.
[0019] In some embodiments, the method further comprises mixing a lithium salt with graphite prior to mixing with the polymer and milling the mixture to produce the lithium salt-graphite composite. In one particular embodiment, the lithium salt comprises two or more lithium salts, typically lithium halide salts.
[0020] In one particular embodiment, the lithium salt is a mixture of lithium bromide and lithium chloride, the molar ratio of lithium bromide to lithium chloride being about 5:1, typically about 3:1, often about 2:1, and most often about 1:1.
[0021] In yet another embodiment, the mass ratio of the lithium bromide to the lithium chloride to the graphite is about 2:0.25:2, typically about 2:0.5:2, and often about 2:1:2.
[0022] In yet another embodiment, the polymer comprises poly(vinylidene fluoride) (PTFE), polyvinylidene fluoride (PVDF), polyvinylpyrrolidone (PVP), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), alginic acid, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, or mixtures thereof. In one particular embodiment, the polymer comprises PTFE.
[0023] In another embodiment, the weight ratio of the lithium salt-graphite composite to the polymer is about 90:10, typically about 92:8, often about 94:6, and most often about 95:5.
[0024] Yet another aspect of the present invention provides a rechargeable lithium ion battery comprising: (i) a composite cathode comprising at least one lithium salt and graphite, wherein the composite cathode is configured such that the lithium salt is oxidized and an oxidation product of the lithium salt is intercalated within the graphite; (ii) an aqueous electrolyte; and (iii) an anode comprising a highly fluorinated polymer.
[0025] In some embodiments, the aqueous electrolyte comprises a water-in-two-salt electrolyte (WiBS). In one particular embodiment, the WiBS is selected from the group consisting of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluoro(oxalato)borate (LiDFOB), lithium hexafluoroarsenate (LiAsF 6), asymmetric ammonium salts (Me3EtN·TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (pyr13TFSI), other ionic liquids or mixtures thereof.
[0026] In another embodiment, WiBS can also include an organic solvent. Suitable organic solvents include, but are not limited to, trimethyl phosphate, ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), γ-butyrolactone (γ-BL), ethyl methyl carbonate, dimethoxyethane, diglycol methyl ether, fluoroethylene carbonate (FEC), and derivatives thereof, as well as other organic solvents known to those skilled in the art or used in lithium ion batteries. See, for example, Long et al., "Polymer electrolytes for lithium polymer batteries," J. Mater. Chem. A, 2016, 4, pp. 10038-10069, which is incorporated herein by reference in its entirety. When organic solvent is present, the amount of organic solvent used relative to water is about 66% or less by volume (i.e., 2:1 or less), typically about 50% or less by volume (i.e., 1:1 or less), and often about 20% or less by volume (i.e., 1:4 or less).
[0027] In yet another embodiment, at least a portion of the lithium salt is phase separated from the aqueous electrolyte.
[0028] In another embodiment, the anode is protected by the fluorinated polymer. In some embodiments, the fluorinated polymer is a fluorinated ether polymer. In another embodiment, the fluorinated polymer comprises a highly fluorinated ether (HFE) polymer gel (e.g., 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, or mixtures thereof). [Brief description of the drawings]
[0029] [Figure 1] Schematic diagram of the conversion intercalation mechanism occurring in the LBC-G complex upon its oxidation in WiBS aqueous gel electrolyte. A two-step reaction involved the oxidation of Br- (~4.0 V) and Cl- (~4.2 V) and their subsequent intercalation into the graphite structure. Discharging was a complete reversal of the loading process. [Diagram 2] FIG. 13 shows cyclic voltammograms of the LBC-G cathode between 3.2 V (vs. Li / Li+) and 4.9 V (vs. Li / Li+) at a scan rate of 0.05 mVs-1. [Diagram 3] Galvanostatic charge-discharge profiles of the LBC-G cathode at a current density of 80 mA g-1. Inset: discharge capacity retention and coulombic efficiency. [Figure 4] Linear sweep voltammetry of pure graphite electrodes (with only PTFE binder) on Ti mesh current collectors in LiBr·3H2O, LiCl·3H2O, and WiBS electrolytes using an Ag / AgCl electrode as reference at 1 mV / s shows that no side reactions, including corrosion of the current collector and oxidation of graphite and water, occur before the onset at approximately 4.0 V (vs. Li / Li+), 4.5 V (vs. Li / Li+), and 5.0 V (vs. Li / Li+) by oxidation of Br-, Cl-, and water, respectively. [Diagram 5]Figure 1 shows the GITT characteristics of the LBC-G cathode at a current density of 80 mA g-1. The red curves are the quasi-equilibrium potentials at various lithiation / delithiation stages, constructed from the average values of each open circuit voltage period during charging and discharging. Inset: Finite diffusion coefficients of reactants D estimated from GITT and EIS measurements. [Figure 6] Nyquist plots of the LBC-G cathode obtained by EIS testing at various SOCs in a three-electrode cell. The dashed lines are the fitted curves using an equivalent circuit. Inset: full-scale plot. [Figure 7] Figure 14. In situ Raman spectra (100 cm-1-550 cm-1) of LBC-G throughout the charge-discharge cycle, showing the evolution of Br2 and BrCl intercalants. Red line: free BrCl signal detected only after intentionally destabilizing the graphite host with a strong laser beam, further confirming the intercalation of BrCl. The quartz background has been removed. [Figure 8] (2b) Ex situ XANES at the Br K-edge of the LBC-G complex during the first charging process. Chemically intercalated Br2 and liquid Br2 (dashed curve) as control samples were measured in the same cell configuration. [Figure 9] FIG. 2c shows ex situ XANES at the Cl K edge of the LBC-G complex during the first charging process. [Figure 10] Figure 1 shows the charge-discharge profiles of the LBC-G composite with various LiBr / LiCl molar ratios after the first charge at a current density of 80 mA g-1. The specific capacity was estimated from the weights of LiBr and LiCl. The molar ratio was only changed by subtracting a portion of LiCl from the original LiBr / LiCl / graphite composite. [Figure 11]Figure 2f shows the charge-discharge profiles of the LBC-G composite with various LiBr / LiCl molar ratios after the first charge at a current density of 80 mA g-1. The specific capacity was estimated from the weights of LiBr and LiCl. The molar ratio was only changed by subtracting a portion of LiBr from the original LiBr / LiCl / graphite composite. [Figure 12] Figure 3a shows the in situ Raman spectra (1200 cm-1 to 2850 cm-1) of LBC-G throughout the charge-discharge cycle, illustrating the change in graphite structure with intercalation / deintercalation of Br2 and BrCl. [Figure 13] Ex situ XRD of the LBC-G composite at various charge-discharge stages in the second cycle (3b). The θ-2θ scan mode was employed with Cu Kα radiation (1.5418 Å) in reflection geometry. Left: full spectrum. Middle: zoom in the range of 2θ (24°-28°). Right: zoom in the range of 2θ (48°-60°). The peaks of the titanium current collector were used to calibrate the diffraction angles. [Figure 14] Figure 3c shows in situ XRD patterns of the (0 0 m+1) peak for the LBC-G composite during charge-discharge cycling, collected by high-energy X-ray irradiation (wavelength 0.1173 Å) in transmission geometry. Left: corresponding voltage profile. Right: 2D contour plot of the XRD pattern and representative curve showing the continuous change in d-spacing of the graphitic host (from 3.30 Å to 3.55 Å) during intercalation / deintercalation. For convenience, 2θ diffraction angles were converted to d-spacings (see Methods). [Figure 15] 3d shows ex situ high-energy XRD patterns of the LBC-G composite (electrolyte and current collector removed) at 50% and 100% SOC. High-energy penetrating X-ray irradiation (0.1173 Å) was set perpendicular to most of the graphite flask to reveal in-plane structural features. [Figure 16]Figures 16A and 16B show the best fit modes of the Br EXAFS experimental data of C7[Br] in stage II (Figure 16A, SOC = 50%) and C3.5[Br0.5Cl0.5] in stage I (Figure 16B, SOC = 100%), respectively. The EXAFS spectra in R space here are not phase corrected, and the distances R for the two stages in the two figures are not comparable, but both are smaller than the actual values. Inset: In-plane structures of C7[Br] in stage II and C3.5[Br0.5Cl0.5] in stage I obtained from DFT simulation. Two sets of bond distances are shown as red (short) and blue (long) lines. [Figure 17] 4a shows typical charge-discharge voltage profiles (3rd cycle) of two Li-ion full cells with an LBC-G cathode made of anhydrous LiBr / LiCl (blue) or LiBr / LiCl monohydrate (red) and a graphite anode protected with HFE / PEO. Charge and discharge were performed at 25° C. and 0.2 C (44 mA g-1 for the LBC-G cathode). Cell capacity was calculated based on the mass of the cathode only (upper x-axis) or the combined mass of the cathode and anode including the binder and protective coating (lower x-axis). [Figure 18] 4b is a graph showing the discharge capacity (relative to the combined mass of the cathode and anode, open circles) and coulombic efficiency (semi-filled circles) of a full cell during cycling in one particular embodiment of a lithium-ion battery of the invention. [Figure 19] FIG. 4c shows the discharge capacity calculated based on the combined anode and cathode mass at various rates for a LBC-G / graphite full cell of one particular embodiment of the present invention having various electrolyte / electrode (cathode+anode) mass ratios. [Figure 20] FIG. 14 shows the galvanostatic charge-discharge profiles of the LBC-G cathode in 4 m LiBF4 / DME electrolyte at a current density of 80 mA g-1. [Figure 21] FIG. 1 shows galvanostatic charge-discharge profiles of LBC-G cathode in Nafion solid electrolyte at a current density of 80 mA g-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] In some embodiments of the present invention, lithium batteries are provided having a capacity (based on the total weight of the composite electrode) of at least about 200 mAh / g, typically at least about 210 mAh / g, often at least about 220 mAh / g, in most cases at least about 230 mAh / g, and in most cases at least about 240 mAh / g. In another embodiment of the present invention, a lithium battery having a capacity of at least about 4.0 V(Li / Li + ), typically at least about 4.1 V (Li / Li + ), usually at least about 4.2 V (Li / Li + The present invention provides a lithium battery having an average potential of 1.0 V vs.
[0031] Such high capacity and / or high potential lithium batteries are made possible by the inventors' discovery of a new electrode in which lithium salts are intercalated within graphite. Without being bound by theory, it is believed that in the lithium batteries of the present invention, the anion redox reactions occur within the graphite lattice and the oxidized anions are stabilized by intercalation into the graphite lattice, thereby avoiding the problems associated with conventional batteries utilizing intercalation cathode chemistries.
[0032] In conventional intercalation cathode chemistries used in Li-ion batteries (LIBs), Li + In its lattice, it stores electrical energy by accommodating Li and replenishes the charge from the cationic redox reactions of transition metals (e.g., Ni, Co, Mn, Fe, etc.). This occurs with good reversibility (long cycle life), but the inserted Li +It has a high molar mass per unit area and may be structurally unstable upon over-delithiation, resulting in relatively low capacity. Furthermore, by providing an environment for the battery's anion redox reactions to occur in the intercalation host, it is believed that both high energy of the anion redox conversion reaction and good reversibility from the topotactic mechanism of intercalation can be obtained.
[0033] For the sake of brevity and clarity, the present invention will be described below with reference to the use of a composite electrode comprising graphite with a lithium halide salt, in particular a combination of lithium bromide and lithium chloride. However, it will be understood that the scope of the present invention is not limited to a lithium salt-graphite composite electrode. In general, the present invention can use any combination of electrode material and anion salt that undergoes an anion redox reaction within the crystal lattice of the electrode material and stabilizes the oxidized anion within the crystal lattice of the electrode material.
[0034] In some embodiments, the lithium-ion battery of the present invention comprises a water-in-two-salt (WiBS) electrolyte. It is believed that the WiBS electrolyte enables or promotes conversion intercalation reactions. Unless otherwise stated or the context requires otherwise, "conversion reaction" as used herein refers to an anion oxidation reaction, such as the conversion of bromide ions to bromine gas, or the conversion of chloride ions to chlorine gas, or the conversion of a mixture of bromide ions and chloride ions to bromine gas, chlorine gas, and / or Br-Cl gas.
[0035] Some embodiments of the present invention include a halide anion (Br - and Cl - ) anion redox reaction. In particular, it is believed that both the anion redox reaction of the halide anion and the resulting oxidation product remain intercalated or entrapped within the lattice of the electrode, e.g., graphite. In one particular embodiment of the invention, graphite with an equimolar lithium halide salt ((LiBr) 0.5 (LiCl) 0.5A composite electrode containing LiBr-graphite (hereinafter referred to as LBC-G) was prepared as an active material. In some embodiments, a WiBS electrolyte is used in the lithium battery of the present invention. It is believed that the high concentration WiBS electrolyte confines at least a portion of the hydrated LiBr and LiCl inside the solid cathode matrix. The anion redox reaction, i.e., oxidation products of bromide and chloride anions, e.g., Br 0 and Cl 0 It is believed that oxidation to takes place within the graphite lattice, with the oxidation products being stabilized by intercalation into the graphite structure.
[0036] In another aspect of the invention, a lithium ion battery is provided that utilizes dense packing of halide ions and a water-in-salt electrolyte to achieve potentials of greater than 4 volts in aqueous batteries. It is believed that the lithium salt in the graphite lattice is phase separated from the aqueous electrolyte. Thus, in another aspect of the invention, a rechargeable lithium ion battery is provided in which at least a portion of the lithium salt is phase separated from the aqueous electrolyte. Phase separation of at least a portion of the lithium salt from the aqueous electrolyte prevents diffusion or shuttle of halide anions and oxidation products of halide anions, thereby significantly extending the cycle life of the battery. When referring to a battery, the term "cycle life" is defined as the total number of recharges while maintaining a coulombic efficiency of at least 99%, typically at least 99.5%, and often at least 99.9%. Alternatively, the term "cycle life" refers to the total number of cycles that a battery can be recharged before the capacity of the battery drops or declines to less than about 80%, typically about 85%, and often about 90% of its theoretical capacity. When referring to a battery, the term "cycling" refers to recharging the battery, typically from about 5% or less of charge to at least about 90% of charge. Thus, one of skill in the art can readily determine the "cycle life" of a battery by depleting the charge of the battery to about 5% or less of theoretical charge, recharging the battery to at least about 90% of theoretical charge, and repeating the process until either the coulombic efficiency or capacity of the battery falls below the amounts specified herein.
[0037] Moreover, in some embodiments, the lithium batteries of the invention have a capacity retention after 100 cycles of at least about 70%, typically at least about 75%, often at least about 80%, most often at least about 85%, and most often at least about 90%.
[0038] In still yet another embodiment, the lithium batteries of the invention have a capacity retention of at least about 80%, typically at least about 85%, often at least about 90%, and in most cases at least about 95% after 100 cycles.
[0039] In another embodiment, the lithium batteries of the invention have a coulombic efficiency over their cycle life of at least about 80%, typically at least about 85%, often at least about 90%, in most cases at least 95%, and in most cases at least about 98%. In yet another embodiment, the lithium batteries of the invention have a coulombic efficiency over their cycle life of at least 99%, typically at least 99.5%, and in most cases at least 99.9%.
[0040] In a further embodiment, the lithium battery of the present invention has a capacity of at least about 250 Wh kg -1 , typically at least about 300 Wh kg -1 , usually at least about 350 Wh kg -1 , in most cases at least about 400 Wh kg -1 , in most cases at least about 450 Wh kg -1 It should be understood that the scope of the invention is not limited to these specific energy densities. In practice, the energy density of a particular battery of the invention will depend on a variety of factors, including, but not limited to, the lithium salt(s), the anode material, the aqueous electrolyte, etc.
[0041] 4.0 V(Li / Li + )~4.5 V(Li / Li +At high delithiation / lithiation potentials (relative to 1000 mAh g), the theoretical energy capacities for LiBr and LiCl are 309 mAh g, respectively. -1 and 632 mAh g -1 These theoretical energy capacity and potential values are much higher than other anions, such as sulfur at about 2.2 V or oxygen at about 3.0 V. The reversible redox reaction of these halide anions and their subsequent intercalation into graphite results in densely packed stage I intercalation compounds C. 3.5 [Br 0.5 Cl 0.5 This is equivalent to 243 mAh g (based on the total mass of the LBC-G cathode). -1 By combining the protected graphite anode disclosed by the inventors (see Yang, C. et al., 4.0 V Aqueous Li-Ion Batteries. Joule 2017, 1, 122-132) with the LBC-G cathode, a 4.0 V class aqueous full cell was fabricated, surpassing most of the current state-of-the-art LIBs (300 Wh kg -1 ~400Wh kg -1 ) with a much higher energy density (460 Wh kg -1 Some of the many advantages of the rechargeable Li-ion battery of the present invention, along with this previously unseen high energy density, include the inherent safety due to its aqueous nature and the much lower cost of the halide active materials compared to various transition metal oxides.
[0042] Halide anions (Br - and Cl - ) was used to prepare graphite with equimolar lithium halide salts ((LiBr) 0.5 (LiCl) 0.5 A composite electrode containing LiBr-graphite (hereinafter referred to as LBC-G) as the active material was prepared. The high concentration WiBS electrolyte confines partially hydrated LiBr and LiCl inside the solid cathode matrix and displaces Br 0and Cl 0 The potential of Li / Li is 4.0 V (Li / Li), which is higher than the potential of sulfur (about 2.2 V) or oxygen (about 3.0 V). + )~4.5 V(Li / Li + At high delithiation / lithiation potentials of 309 mAh g for LiBr, -1 Theoretical capacity of 632 mAh g for LiCl -1 The reversible redox reaction of these halide anions and their subsequent intercalation into graphite provides a densely packed stage I intercalation compound, C 3.5 [Br 0.5 Cl 0.5 This is equivalent to 243 mAh g (based on the total mass of the LBC-G cathode). -1 Supports the full capacity of
[0043] By combining the protected graphite anode disclosed by the inventors (see Yang, C. et al., 4.0 V Aqueous Li-Ion Batteries. Joule 2017, 1, 122-132) with the LBC-G cathode, a 4.0 V class aqueous full cell was fabricated, surpassing most of the current state-of-the-art LIBs (300 Wh kg -1 ~400Wh kg -1 ) with a much higher energy density (460 Wh kg -1 Some of the many advantages of the rechargeable Li-ion battery of the present invention, along with this previously unseen high energy density, include the inherent safety due to its aqueous nature and the much lower cost of the halide active materials compared to various transition metal oxides.
[0044] This conversion intercalation LBC-G chemical structure is PF 6 - , B.F. 4 - , TFSI -The LBC-G cathode is distinct from all other graphite intercalation chemistries with anions such as Br, ... - and Cl - ) in the LBC-G. Therefore, in principle, the capacity is not limited by the solubility of the salt or the amount of electrolyte. Secondly, upon charging, the oxidized species in LBC-G are bromide / chloride anions, and the graphite host remains largely intact, whereas the graphite cathode in the so-called "dual-ion" battery becomes oxidized by hosting electron holes and anion intercalants (PF 6 - , B.F. 4 - , TFSI - ) maintains its chemical state. Due to the near-zero oxidation state in graphite, the Coulomb repulsion between the Br and Cl intercalants is small, and the C 3.5 It has become possible to prepare high density graphite intercalation compounds (GICs) of [H] (H = halogen). This is because 24 + [X - ] or C 20 + [X - ](X - =PF 6 - , B.F. 4 - , TFSI - Only dilute GICs with the general formula (e.g., -1 This is in sharp contrast to "dual-ion" batteries, which can be made with capacities below 1000V. Also, the LBC-G chemistry uses transition metal halides (FeF 2 , CuF 2 etc.) and anion redox couples (S / Sn 2- , O / O 2- , Br 3 - / Br -It also differs from traditional conversion cathodes such as the anion redox couple (S / Sn etc.). Compared to transition metal halides, the anion redox potential and energy are much higher than those of the transition metal cation redox. Furthermore, the intercalation of halogens into graphite in LBC-G is much faster and more reversible than the crystal rearrangement reaction in transition metal halides. This crystal rearrangement reaction is often accompanied by large rate hysteresis, large volume changes, and irreversible particle collapse. The anion redox couple (S / Sn 2- , O / O 2- , Br 3 - / Br - For other materials, the reaction rate has also been improved by dissolving the intermediates, but the final charging products are usually deposited or adsorbed on the high surface area carbon host, leading to side reactions, parasitic shuttle effects, and low volumetric energy density. By using ultra-high concentration WiBS electrolyte, the halide anions in the hydration layer, which are thermodynamically immiscible with WiBS, can be trapped within the cathode solid composite during repeated cycling of LBC-G, and the highly reactive oxidation product (BrCl, gaseous at room temperature) can be effectively stabilized by intercalation into graphite, thereby ensuring the high reversibility of this conversion intercalation chemistry.
[0045] Anhydrous LiBr and anhydrous LiCl were added to the graphite powder in a mass ratio of 2:1:2 ((LiBr) 0.5 (LiCl) 0.5 C 3.7 The LBC-G composite cathode was fabricated by mixing the working electrode and Ag / AgCl (corresponding to a molar ratio of 0.1 to 0.25) with activated carbon (approximately 50 times the mass of the working electrode) as the counter electrode, Ag / AgCl as the reference electrode, and 80 wt % of WiBS aqueous gel polymer (21 mol kg lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)) as the electrolyte. -1 , lithium trifluoromethanesulfonate (LiOTf) at 7 mol kg -1The LiBr-LiCl salt in the LBC-G was evaluated in a three-electrode cell using WiBS electrolyte (20 times the mass of the working electrode) and 20 wt. % polyethylene oxide (PEO). Upon exposure to WiBS electrolyte (20 times the mass of the working electrode), the anhydrous LiBr-LiCl salt in the LBC-G extracted traces of water (approximately 2.4%) from the WiBS and formed a hydrated LiBr-LiCl layer on the surface of the LBC-G (estimated overall formulation is LiBr 0.34 H 2 O-LiCl 0.34H 2 O), which promotes the redox reactions of halogens in the form of solvated anions. Figure 1. Meanwhile, this hydrated salt layer is thermodynamically phase separated from the bulk WiBS electrolyte, creating a dynamic water equilibrium. Such a liquid layer allows the formation of LiCl and LiBr, as evidenced by MD simulations and the extremely low Cl and Br contents (less than 32 ppm) detected by chromatographic analysis in the WiBS electrolyte equilibrated with LiCl-LiBr solution for 500 h. + The transport of halide ions is permitted while preventing diffusion and possible undesired shuttle of halide ions.
[0046] Cyclic voltammetry (Fig. 2) and charge / discharge profile (Fig. 3) of LBC-G show that Br - 4.0 V for intercalation (Li / Li + )~4.2 V(Li / Li + ) and Cl - 4.2 V for intercalation (Li / Li + )~4.5 V(Li / Li + This gives a total mass of 243 mAh g (relative to the total mass of the LBC-G complex containing the LiBr / LiCl salts and graphite). -1 A high reversible discharge capacity of 82% was obtained at a current density of 80 mA g -1 (0.2 C) for 230 cycles with 100% coulombic efficiency maintained after the 80th cycle. This two-step redox reaction corresponds to: LiBr+C n ⇔Cn [Br]+Li + +e - 4.0V~4.2V (1) LiCl+C n [Br]⇔C n [BrCl]+Li + +e - 4.2V~4.5V (2) where n is the molar ratio of carbon atoms to the inserted halogen in the GIC. During the charging process, the Br in the hydration layer, which has a relatively low redox potential, - First, the oxidation valence (Br 0 ), which is electrochemically oxidized to C, and intercalated into the nearby graphite interlayers. n [Br] as Br 2 GIC is formed (Equation 1). Further charging leads to Cl at a higher potential. - Oxidation of Cl 0 Intercalation of the mixed intercalation compound C occurs in the hydration layer (Equation 2). This has never been observed before, and this allows the intercalation of the mixed intercalation compound C n [BrCl] is formed. The oxidation of each halogen involves the transfer of one electron, providing the same molar volume for each of Br and Cl. At the same time, Li + is transferred to the bulk electrolyte and reduced at the anode. During the discharge process, the reverse reaction occurs: Cl and Br are subsequently desorbed from the graphite interlayer and reduced back to Li. + and LiBr to form solid LiCl and LiBr crystals and liquid halides outside the graphite host. Thus, all the active materials LiCl and LiBr are well retained within the solid electrode, and no significant loss occurs due to dissolution and shuttle. The thermodynamic reaction potential of LBC-G was confirmed by density functional theory (DFT) calculations. The fully charged product C of the LBC-G complex 3.5 [Br 0.5 Cl 0.5 ] has a capacity of 251 mAh g at an average potential of about 4.2 V. -1 In this conversion intercalation chemistry, the WiBS electrolyte achieves a theoretical storage capacity of approximately 4.9 V(Li / Li +1This plays a role in electrochemical reversibility since the halogen atoms are not oxidized until the potentials reach 4.0 V (relative to the potential of the Ti current collector). This allows the oxidation / reduction of halides, which occurs at intermediate potentials (4.0 V to 4.5 V), to be reversible. As shown in Figure 4, the Ti current collector and graphite remain intact at the operating potentials while only the halogens are oxidized.
[0047] The galvanostatic intermittent titration method (GITT) was used to study the quasi-equilibrium potential and reaction rate at various stages. - The voltage for the oxidation / intercalation reaction of Cl is about 4.05 V. - The potential for the oxidation / intercalation reaction of ZnO is approximately 4.35 V (Figure 5). On the other hand, the total diffusion coefficient is 10 -15 cm 2 s -1 ~10 -13 cm 2 s -1 The diffusion coefficient of the LBC-G cathode was estimated to be in the range of 1000 Hz (red and blue curves in the inset of Fig. 5). The diffusion coefficient of the LBC-G cathode was also investigated using electrochemical impedance spectroscopy (EIS). Here, the Nyquist plot (Fig. 6) showed two semicircles with characteristic frequencies at about 1250 Hz and 20 Hz, respectively. The semicircle at high frequency is due to the charge transfer resistance on the surface of the graphite matrix, the semicircle at mid frequency corresponds to the dissolution / precipitation of salts in the hydration layer and the finite diffusion of reactants, and the sloping tail at low frequency is due to halogen diffusion in the graphite. By fitting the Nyquist plot with an equivalent circuit, the apparent ionic diffusion coefficient of the reactants (including dissolution / precipitation) was found to be 6.85 × 10 -15 cm 2 s -1 ~2.07×10 -14 cm 2 s -1 (green circle in the inset of Fig. 5), which is in excellent agreement with the total diffusivity values estimated from the GITT measurements. Considering the extremely high diffusion coefficients of halogens in the graphite interlayer, it is expected that the diffusion of Br between the solid salt and the graphite surface is - and Cl -The mass transfer of constitutes the rate-limiting step in this chemical structure, which was also evidenced by the finite diffusion behavior.
[0048] The LBC-G is a 4.2 V (Li / Li + Average discharge voltage of 231 mAh g (total weight of electrode) -1 Practical gravimetric capacity, (based on total electrode volume) 450 mAh mL -1 It provides a volumetric capacity of 970 Wh kg -1 This results in an extremely high energy density of 1000 times that of Ni-, Co-, and Mn-based intercalation cathode materials, or comparable to sulfur conversion cathodes. However, the volumetric energy density of LBC-G is much greater than that of sulfur. The nature of the conversion intercalation of LBC-G, with both high gravimetric and high volumetric energy densities, makes it one of the most useful cathode chemistries for lithium-ion batteries.
[0049] To investigate the mechanism of intercalation of halogen species during charging and discharging of LBC-G, in situ Raman spectroscopy (100 cm -1 ~550 cm -1 ) was performed (Figure 7). When the state of charge (SOC) was between 0% and 50%, a characteristic peak (ω 0 =242 cm -1 ) was detected. This is due to the fact that Br 2 This corresponds to the stretching mode of the molecule. Upon further charging, a new characteristic peak (ω 0 =310 cm -1 ) was introduced. This was verified by a reference made by chemical intercalation of BrCl into graphite. The peak intensity of the BrCl intercalant increases with charging LBC-G up to 4.5 V. Charge transfer through the graphene layer weakens the interatomic bonds of the halogen intercalant. This causes the frequency to shift to the free Br 2 318 cm for molecules (liquid) -1 From Br 2242 cm for Intercalant -1 downshifted to 427 cm for the free BrCl molecule (gas) -1 from 310 cm for BrCl intercalant -1 During charging and discharging between 3.2 V and 4.5 V, the free BrCl GIC remains stable unless the fully intercalated BrCl GIC is intentionally destabilized by a high-intensity laser beam. 2 Note that no peaks of free BrCl or free BrCl were detected (red curve, Figure 7). It is believed that all halogens generated by the redox reaction of halide anions were inserted into the graphite structure, rather than simply adsorbed on the surface of the graphite flakes. Upon the discharge process, a completely reversible change was observed in the Raman spectrum.
[0050] The oxidation states of halogens at various SOCs, reflecting the redox reaction sequence in the LBC-G cathode, were monitored using ex situ X-ray absorption near edge structure (XANES) spectra. In the case of Br K-edge, a clear and sharp peak at about 13473 eV, attributed to the 1s → 4p transition in Br atoms, appeared immediately after charging the LBC-G cathode, see Figure 8. The peak intensity of this "white line", reflecting the hole density in the Br 4p orbital, gradually increased with a blue-shifted absorption edge (1s → continuum, about 13480 eV). From the beginning of the charging process, the Br - takes the hole, and Br 0 In the case of the Cl K-edge (Figure 9), only a single absorption edge (1s → continuum) at about 2825 eV was observed during the first charge plateau (SOC: 0%-50%), indicating that all Cl remained in the -1 oxidation state. As indicated by the appearance of a "white line" peak (at about 2821 eV) due to the 1s → 3p transition in Cl atoms, the Cl K-edge peak in the LBC-G cathode was significantly increased. - The oxidation of Br appears to occur only at the second charge plateau (SOC: 50%–100%). 2 and liquid Br 2Compared with the reference spectrum (dashed line in Figure 8), Br appears to be almost completely oxidized, but Br is not completely oxidized during the first charge plateau (SOC: 0% to 50%). 0 According to the distribution of electron density in the DFT simulation, the oxidation state of Br was 50% at Br 2 The GIC remains at approximately -0.16. Subsequent inserted Cl tends to combine with previously inserted Br, and the oxidation state of Br is relatively less electronegative compared to Cl, so Br 0 It gets even higher (-0.05) approaching , but the oxidation state of Cl is -0.25.
[0051] This halogen exchange intercalation mechanism in the LBC-G cathode is also supported by the charge-discharge profiles of the LBC-G cathode at various LiBr and LiCl molar ratios. Figures 10 and 11. The capacity ratios of the two charge-discharge plateaus are highly correlated with the LiBr / LiCl molar ratio in the LBC-G cathode, suggesting that the two different potential plateaus are due to the individual redox reactions of Br and Cl, respectively. The specific capacity calculated by the weight of LiBr in the LBC-G cathode at the low potential plateau (below 4.25 V, Figure 10) at a low rate of 0.2 C or less is very close to the theoretical redox capacity of LiBr (309 mAh / g). Meanwhile, the specific capacity at the high potential charge plateau (above 4.25 V), calculated based on the weight of LiCl, is close to the theoretical redox capacity of LiCl (632 mAh / g, Figure 11). Interestingly, the coulombic efficiency of the LBC-G cathode at the high voltage plateau increases with increasing LiBr / LiCl ratio. 0 The single intercalation of Br 0 This shows that it is not thermodynamically stable unless combined with the most stable C in graphite. n This is because the intercalation compound of [Br / Cl] is achieved when the LiBr / LiCl ratio is close to 1:1. In sharp contrast, the pure (LiBr)0.5 (LiCl) 0.5 can exhibit high oxidation capacity during initial charge, but the discharge capacity is very low due to loss of gaseous halogen. Carbon hosts can improve reversibility and discharge capacity by surface adsorption of halogen, while further increasing the coulombic efficiency according to their degree of graphitization. Graphite intercalation is believed to provide a reversible and compact way to accommodate the halogen oxidation products.
[0052] In situ Raman spectroscopy (1200 cm -1 ~2850 cm -1 ) showed the structural change of the graphite superlattice during halogen intercalation. Figure 12. The GIC stage number m, defined as the number of unintercalated graphene layers between the two nearest layers where an intercalated guest species resides, provides important information. The graphite G band (1584 cm -1 ) gradually decreases during halogen intercalation (charging) to double (E 2g2 (b) Mode and E 2g2 (i) mode), and at 50% SOC, a peak characteristic of stage II GIC structure (1612 cm -1 , E 2g2 (b) Mode G 2 In the fully charged state, this peak changes to 1631 cm, which indicates a stage I GIC structure. -1 The graphite D band (1350 cm -1 ) disappears immediately after intercalation into the graphite, which is typical of GICs. During the discharge process, a completely reversible change in the Raman spectrum is observed.
[0053] X-ray diffraction (XRD) spectra revealed detailed changes in the stage structure of the LBC-G cathode. Ex situ XRD (reflection geometry, Figure 13) of the LBC-G cathode showed a shifted major peak at (0 0 m+1) and a sub-major peak at (0 0 2m+2) upon halogen intercalation / deintercalation, further confirming the reference pattern. Closer examination revealed that as the SOC of LBC-G increased from 0% to 50%, the d-spacing of the major peak shifted from 3.35 Å for pristine graphite (0 0 2) to 3.5 Å for stage II Br 2 d for GIC 003 The intercalation of Cl gradually reduces the d-spacing due to the slightly lower height of the intercalant gallery, and finally leads to the formation of stage I BrCl GICs (d 002 It is believed that the intercalation temperature reached approximately 3.43 Å, which is consistent with the intercalation process revealed by Raman spectroscopy. In situ XRD (Figure 14) of the LBC-G cathode showed that the (0 0 m+1) d-spacing shifted continuously during charging and discharging. This indicates that the graphene interlayer gradually expanded due to the accommodation of halogen atoms. A complete reversal of the above-mentioned progression was observed again during the discharge process. This indicates that the graphitic structure was fully restored after deintercalation, which provides the basis for excellent reversibility. The formation of the highest concentration of GIC in stage I ensures the high capacity of the LBC-G conversion intercalation chemical structure. The proposed reaction mechanism in reaction 1 and reaction 2 is confirmed by the consistency between the stage numbers of the LBC-GIC and the corresponding charge-discharge capacities.
[0054] The in-plane structure and coordination of the halogen intercalants in the GIC provide a method to determine the optimal intercalation concentration for the LBC-G cathode chemistry. Since the in-plane intercalation structure was independent of the intercalation concentration, C n [Br] and C nThe stoichiometry n of [BrCl] always remains the same in each intercalation domain, regardless of the overall intercalation concentration. Ex situ high-energy XRD (normal incidence) (Fig. 15) of the LBC-G cathode (after removal of the electrolyte and current collector) at 50% and 100% SOC (after removal of the electrolyte and current collector) showed asymmetric and overlapping peaks in addition to those specific to the graphene layers and the PTFE binder, revealing an intermediate level of long-range order in the intercalant in-plane structure. At 50% SOC, single crystal Br 2 According to the GIC reference, only three peaks at low diffraction angles can be indicative. This indicates multiphase coexistence, local disorder, and structural distortion. From the DFT simulations, multiple possible in-plane structures were predicted based on two stoichiometries, n, integer multiples of 7 and 8. All predictions revealed zigzag polymer-like chains of -Br-Br- or -Br-Cl- with shortest in-plane distances between 2.4 Å and 3.2 Å (insets in Figures 16A and 16B). Interestingly, all of these models have very similar potentials (within 20 mV), indicating that the real material may be slightly disordered due to the coexistence of these idealized model structures, as evidenced by the ex situ XRD patterns (Figure 15). From the molecular dynamics simulations, it is predicted that a slight Br excess or close Br-Br contacts due to interactions between adjacent intercalant chains may lead to disorder in the overall structure. However, after a brief annealing at 360 °C and relaxation to 60 °C, an additional simulation for 100 ps under constant pressure conditions did not show any signs of gas evolution and subsequent graphite exfoliation.
[0055] By fitting the Br extended X-ray absorption fine structure (EXAFS) data of the LBC-G cathode at 50% and 100% SOC (FIGS. 16A and 16B, respectively), the most suitable model was C 7m [BrBr] and C 7m [BrCl]. Both were C 8m [BrBr] and C 8mInstead of a consistent distance for [BrCl], there were two sets of shortest in-plane distances (Br-X1 and Br-X2, where X = Br or Cl). Due to interactions with the π electrons of the graphene plane, the average shortest in-plane distances of the halogen intercalants were 2.50 Å for Br-Br1 and 3.15 Å for Br-Br2, while they were 2.43 Å for Br-Cl1 and 3.00 Å for Br-Cl2. 2 These shortest in-plane distances are longer than the bond distances of the free molecules (approximately 2.30 Å) and the free molecules of BrCl (2.18 Å). However, these shortest in-plane distances are shorter than the GICs of alkali metals (4.31 Å to 4.92 Å) and large anions (e.g., PF 6 - , B.F. 4 - , TFSI - , 8 Å-10 Å), which gives the halogen intercalants one of the highest in-plane densities of all reported GICs. Without being bound by theory, it is believed that this dense packing is primarily due to the near-zero oxidation valence of the halogen intercalants. This creates much lower Coulombic repulsions with an average effective charge per halogen atom of about -0.16, compared to >+0.90 for Li GICs and -1 for large anions.
[0056] An aqueous LIB full cell was constructed by combining an LBC-G cathode with a graphite anode protected by a highly fluorinated ether (HFE) polymer gel using an aqueous gel electrolyte derived from WiBS. A stable discharge capacity of 127 mAh / g (relative to the total mass of the anode and cathode) was obtained at an average voltage of 4.1 V at 0.2 C (Figure 17), and 74% of this initial capacity was retained over 150 cycles with an average coulombic efficiency of 99.8% (Figure 18). The low self-discharge rate indicated that the ultra-high concentration aqueous gel electrolyte effectively suppressed undesired reactions, especially the decomposition of water and the loss of halogen active material from the cathode.
[0057] The mass ratio of WiSB electrolyte to cathode can affect the rate performance of the LBC-G cathode, since the extraction of 2.4 mol% water from WiBS to form a hydrated LiBr / LiCl layer is important to achieve high power density. As shown in the top of FIG. 19, the rate capacity was compromised when the electrolyte / electrode (cathode+anode) mass ratio was reduced from 4:1 to 1:2. Thus, in some embodiments, the electrolyte / electrode ratio is about 1:1, typically about 2:1, and often about 4:1. On the other hand, a higher electrolyte to electrode ratio would result in a lower energy density. One solution is to use LiBr monohydrate and LiCl monohydrate (LiBr·H) when fabricating the LBC-G cathode. 2 O and LiCl H 2 The first step is to use LiBr H to replace its anhydrous salt. This would eliminate the strong reliance on the WiBS electrolyte as the water source. The LBC-G cathode with the monohydrate showed almost the same charge-discharge profile as the anhydrous one at a low rate of 0.2 C, except for a slightly lower specific capacity (Figures 17 and 18) due to the additional water mass provided by the monohydrate. However, the LiBr H 2 O-LiCl H 2 The rate capacity of the OG / / G full cell is much higher than that of the anhydrous one, and the effect of the electrolyte / electrode mass ratio is minimal. Because the performance of the cell constructed with LiBr-LiCl monohydrate does not depend on the amount of electrolyte, the energy density of such an aqueous LIB is about 460 Wh kg for the total mass of the cathode (including the monohydrate) and anode. -1 Such an energy density has not been reported for any known aqueous battery and is even higher than all known non-aqueous LIBs of the current state of the art. Taking into account the mass of the electrolyte, the energy density of the full cell is 304 Wh kg -1 It is noted that this high energy density is accompanied by inherent safety and low environmental impact due to its aqueous nature. The new aqueous cathode chemistry disclosed herein provides for a battery with higher energy while being cost-effective, safe, and flexible.
[0058] A non-aqueous LIB coin cell was constructed by combining an LBC-G cathode with a lithium anode using a concentrated organic electrolyte. The current density was 80 mA g -1 A high discharge capacity of 151 mAh / g (relative to the mass of the cathode) was obtained (Figure 20). As in the aqueous system, the two-step reaction involved the presence of Br -1 (approximately 3.6 V) and Cl -1 The oxidation of Br (at about 3.8 V) and its subsequent intercalation into the graphitic structure. The discharge capacity decreased to 83 mAh / g, which corresponds to 55% of the initial coulombic efficiency. The constant decrease was mainly due to the Br 2 For Nafion solid electrolyte, the dissolution of Br 2 This effectively prevents the dissolution of the electrolyte, resulting in more stable charge / discharge performance (Figure 21).
[0059] Additional objects, advantages, and novel features of this invention will become apparent to those skilled in the art upon examination of the following examples thereof, which are not intended to be limiting, in which procedures presumably carried out are described in the present tense and procedures performed in the laboratory are described in the past tense. EXAMPLES
[0060] Electrode preparation For the three-electrode cell, anhydrous LiBr (99.9%, Sigma-Aldrich), anhydrous LiCl (99.9%, Sigma-Aldrich), and synthetic graphite powder (TIMCAL TIMREX™ KS4, average particle size approximately 4.1 μm) were mixed homogeneously in a zirconia ball mill for 15 min to prepare (LiBr) 0.5 (LiCl) 0.5 The LiBr / LiCl molar ratio was 1:1, and the LiBr / LiCl / graphite mass ratio was approximately 2:1:2. In the full cell containing LiBr / LiCl monohydrate, anhydrous LiBr / LiCl was dissolved in LiBr H 2All procedures were the same except for replacing O (99.95%, Sigma-Aldrich) and LiCl (99.95%, Sigma-Aldrich). Other control samples were obtained by adjusting the complex (LiCl / graphite about 1:3 for LiCl-graphite, (LiBr) 0.5 (LiCl) 0.5 -For Ti, the ratio of LiBr / LiCl / titanium nanopowder is about 2:1:60, (LiBr) 0.5 (LiCl) 0.5 -For AC, the ratio of LiBr / LiCl / activated carbon is approximately 2:1:9, (LiBr) 0.5 (LiCl) 0.5 The ratio of LiBr / LiCl / graphitized acetylene black for -CB was approximately 2:1:9. The LBC-G composite cathode was fabricated by compressing the LBC-G composite and poly(vinylidene fluoride) (PTFE) in a weight ratio of 95:5 on a titanium metal mesh (Alfa Aesar, 100 mesh). The areal loading of the cathode material was approximately 38 mg cm. -2 The thickness of the cathode is about 200 μm. The graphite anode was fabricated using synthetic graphite powder (TIMCAL TIMREX™ KS44, particle size about 45.4 μm) and poly(vinylidene fluoride) (PTFE) in a weight ratio of 9:1 on a stainless steel mesh (200 mesh).
[0061] Preparation of electrolyte First, 21 mol kg -1 of LiTFSI (98%, TCI Co., Ltd.) and 7 mol kg -1 A liquid "water in two salts" (WiBS) aqueous electrolyte was prepared by dissolving 100% LiOTf (99.996%, Sigma-Aldrich) in water (HPLC grade). An aqueous gel electrolyte was prepared by mixing 20 wt. % poly(ethylene oxide) (PEO, average Mv ca. 600000, Sigma-Aldrich) with the WiBS electrolyte and heating at 80 °C for 1 h in a sealed glass mold. After cooling to room temperature, a viscous semi-solid WiBS gel electrolyte was obtained, which can be transformed into any shape at 50 °C.
[0062] HFE-PEO gel protective coatings were prepared. Briefly, the coating gel was prepared by mixing 1,1,2,2-tetrafluoroethyl-2',2',2'-trifluoroethyl ether (Daikin America or Apollo) with 0.5 M LiTFSI (denoted as LiTFSI-HFE gel) and 10 wt% PEO (Sigma-Aldrich) in HFE / FEC (volume ratio = 95:5) and heating at 70 °C for 5 min with stirring.
[0063] Preparation of chemical GIC as a reference sample Chemically intercalated Br according to the reported procedure. 2 GIC and BrCl GIC were synthesized as reference samples. See, for example, Heald, SM & Stern, EA EXAFS study of Br 2 -graphite intercalation compounds. Synthetic Metals 1, 249-255, (1980), and Furdin, G., Bach, B. & Herold, AA, C. R. Acad. Sci., Ser. C 271, 683, (1970). Briefly, a graphite flask (TIMCAL TIMREX™ KS4) was heated with 1000 ml of highly contracted Br in a tightly sealed flask. 2 (99.99%, Sigma-Aldrich) vapor and BrCl gas for 2 h. 2 GIC and BrCl GIC were prepared. BrCl was 2 of the equimolar Cl obtained by the reaction of trichloroisocyanuric acid with hydrochloric acid. 2 and mixed at -70°C.
[0064] Electrochemical measurements In the three-electrode cell, the LBC-G electrode (or other reference electrode) was used as the working electrode, activated carbon was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The mass ratio of the working electrode to the electrolyte was 1:20. The three-electrode cell was then galvanostatically charged and discharged at room temperature using a Land BT2000 battery test system (Wuhan, China). Cyclic voltammetry was performed using a CHI 600E electrochemical workstation. GITT experiments were performed on the three-electrode setup with the same electrode configuration. The cycling protocol consisted of alternating 0.2 C current pulses for 20 min with OCV periods for 120 min to reach a quasi-equilibrium potential. The apparent ion diffusion coefficients (D) of the reactants in the LBC-G cathode at various charge and discharge states were estimated from the GITT measurements using the following relationship:
number
[0065] The full cells were assembled as CR2032-type coin cells using LBC-G as the cathode and either a sulfur-carbon electrode or a graphite electrode as the anode. For the graphite anode cells, the cathode / anode mass ratio was set to 1.38:1. A titanium metal foil disk was applied between the cathode and the coin cell case to prevent corrosion. WiBS gel electrolyte was pressed into a film and applied to the coin cells as both electrolyte and separator. The total electrode-to-electrolyte mass ratio ranged from 1:4 to 2:1. After assembly, the cells were heated to 50 °C for GPE self-repair. The full cells were then galvanostatically cycled at room temperature in a Land BT2000 battery test system (Wuhan, China).
[0066] The specific (weight or volume) energy density (E) of the full cell was calculated from the following formula: E=C×U (4) where C was the specific (gravimetric or volumetric) cell capacity and U was the average output cell voltage. Gravimetric Capacity C m was calculated from the following formula:
number
[0067] In situ Raman and XRD studies For in situ Raman studies, the LBC-G full cell (in coin cell configuration) was charged and discharged at 0.1 C. A quartz optical window (φ=5 mm) was applied to the cathode side. Raman spectra were recorded using a Horiba Jobin Yvon Labram Aramis at 3500 cm -1 ~60cm -1 The data was collected using a laser (wavelength = 532 nm) between 100 and 1500 nm. To obtain a high signal-to-noise ratio, 4 × 4 points of data were collected.
[0068] For ex situ X-ray diffraction (XRD) studies, the LBC-G electrode (working electrode) was retraced from the three-electrode cell after charging and discharging to a certain SOC at 0.1 C. For in situ X-ray diffraction (XRD) studies, the full cell (in coin cell configuration) was charged and discharged at 0.1 C. Kapton windows (φ=3 mm) were applied on both sides of the coin cell, and the anode was intentionally positioned to avoid the beam passing through the window. X-ray diffraction patterns were recorded on a Bruker D8 Advance X-ray diffractometer using Cu Kα radiation in a grazing incidence geometry. High-energy synchrotron XRD measurements were performed at the 11-ID-C beamline at the Advanced Photon Source (APS) at Argonne National Laboratory. Two-dimensional (2D) diffraction patterns were obtained in a transmission geometry using high-energy X-rays with a beam diameter of 0.2 mm × 0.2 mm and a wavelength of 0.1173 Å. X-ray patterns were recorded on a Perkin-Elmer large area detector placed 1800 mm from the battery cell. The interval between the acquired diffraction patterns was 5 min. The acquired 2D diffraction patterns were compared with the standard CeO 2 The samples were used for calibration and converted to 1D patterns using Fit2D software.
[0069] The periodic repeat distance of the GIC (I c ), the height of the intercalant passage (d i ) can be calculated using the following formula: I c =d i +3.35 Å×(m-1)=l×d obs (5) In the formula, l is the index of the (0 0 l) plane oriented in the stacking direction, and d obsis the observed value of the spacing between two adjacent planes in the XRD pattern. It can be calculated from the diffraction angle by Bragg's law. The d-spacing of pristine graphite is 3.35 Å. The intensity pattern is typically seen for graphite intercalation compounds (GICs) at stage m, with the most dominant peak at (0 0 m+1). The d-spacing value of (0 0 m+1) was calculated from the XRD data by Bragg's law. It can be assigned to the most dominant stage phase of the observed GICs.
[0070] Ex situ XANES and EXAFS studies Ex situ X-ray absorption spectroscopy (XAS) measurements were performed with the same cell configuration used for the in situ XRD measurements. The experiments were performed in transition mode at beamline 20-BM-B of the APS at Argonne National Laboratory. XANES measurements were performed at the K-edges of bromine (13474 eV) and chlorine (2825 eV) to monitor the change in valence state of Br and Cl at the cathode, and energy calibration was performed using the first derivative point of the XANES spectrum of Bi (LIII edge = 13419 eV). During Cl measurements, the entire X-ray beam, sample, and detector were protected with helium gas. Reference spectra were collected for each in situ spectrum with bismuth metal foil placed in the reference channel. EXAFS spectra were aligned, integrated, and normalized using Athena. The coin cells were charged at a constant current to a certain voltage before the measurements.
[0071] First, the Athena program was used to process the X-ray absorption experimental data to obtain the normalized vibration amplitude χ exp (k) was extracted. The photoelectron wave number k is
number
number
[0072] SEM imaging and specific surface area measurement SEM of the cycled cathodes was performed using a Hitachi S-4700 operated at 5 kV. The specific surface area of the samples was measured using a Micromeritics ASAP 2020 Porosimeter Test Station (N 2 The samples were characterized by adsorption. Prior to testing, the samples were degassed (in vacuum) at 180° C. for 12 h. The specific surface area was calculated from the adsorption branches using the BET method.
[0073] Molecular dynamics simulation of LiBr in WiSE MD simulations were performed at 363 K for an 18 m (mol salt / kg solvent) LiBr solution and a mixed salt solution of 18 m LiBr + 21 m LiTFSI. For the MD simulations, the previously modified CHARMM H 2 O force field 47 was used in combination with the APPLE&P many-body polarizable force field, which yielded LiTFSI-H, which showed excellent agreement with experiment over a wide salt concentration range from 5 mM to 21 mM. 2 The ionic conductivity of O, the self-diffusion coefficients of ions and water, the viscosity, and the density were predicted.
[0074] For the MD simulations, we use a parallel version of our in-house developed MD simulation package. The 18 m LiBr aqueous solution simulation cell contains 448 LiBr molecules and 1390 H 2 The mixed salt MD simulation cell contained 1380 H 2 The mixture contained 0, 512 LiTFSI, and 448 LiBr. All the (LiTFSI) n (LiBr) m (H 2 O) k The complexes gave large simulation cells of 70 Å and 95 Å. The dimensions of the simulation box were gradually reduced to 60 Å. NPT simulations were performed for 2 ns at 363 K for the mixed salt system using a modified force field that increased the repulsive forces between Br / Br and TFSI / TFSI anions to distribute the anions uniformly throughout the simulation box. After 9 ns of MD simulations in the NPT ensemble, LiBr(H 2 O) n LiTFSI (H 2 O) m Such behavior indicates the early stages of phase separation and is consistent with experimental observations.
[0075] In the MD simulation, the permanent charge with k = 6 3 Ewald summation was utilized to treat electrostatic interactions between permanent charges with vector induced dipole moments. Multiple time step integration was employed with an inner time step of 0.5 fs (bonded interactions), a central time step of 1.5 fs for all nonbonded interactions within the cutoff distance of 7.0 Å to 8.0 Å, and an outer time step of 3.0 fs for all nonbonded interactions between 7.0 Å and the smaller nonbonded cutoff distance of 19 Å. The Ewald reciprocal part was updated only at the largest of the multiple time steps. A Nose-Hoover thermostat and barostat were used to perform 10 -2 fs and 0.1×10 -4 Temperature and pressure were controlled at relevant frequencies of 1000 fs. Atomic coordinates were stored every 2 ps for post-mortem analysis.
[0076] The ability of MD simulations using the atomic dipole polarizable APPLE&P force field to predict the density and conductivity of 18 m aqueous LiBr solutions was investigated at 333 K. After 3 ns of equilibration in the NPT ensemble, 8 ns of MD simulations in the NVT ensemble predicted a density of 1649 kg m -3 This predicted electrolyte density of 1636.5 kg m -3 The ionic conductivity (σ) was extracted using Einstein's relationship shown in the following equation:
number
number
[0077] DFT simulation of intercalation structure configuration All calculations were performed using DFT with the plane wave basis set and the projected augmented wave (PAW) method as implemented in the Vienna Ab Initio Simulation Package (VASP). The Perdew-Burke-Ernzerhof (PBE) functional in the generalized gradient approximation (GGA) was employed to calculate the exchange-correlation energies. An energy cutoff of 580 eV was used for the plane wave basis, and the Brillouin zone was sampled using the Monkhorst-Pack scheme. The van der Waals energies were corrected using the van der Waals density functional (vdW-DF) from optB86b to obtain accurate interlayer spacing values in all cases. C 7 [Br], C 3.5 [Br 0.5 Cl 0.5 ] and C 8 [Br], C 4 [Br 0.5 Cl 0.5 Two sets of possible configurations for [ are considered. In these configurations, the Br and Cl atoms are randomly initialized. The geometry optimization was performed using the conjugate gradient method. The convergence threshold was 10-5 eV and force are set to 0.01 eV / Å. Charge difference plots are 7 [Br](C 3.5 [Br 0.5 Cl 0.5 The charge density of both graphite and Br (BrCl) was obtained from the charge density of Br (BrCl) (Figure 1). The charge distribution on the atoms was determined using the Bader refinement method. Visualization of the structure was performed using VESTA software.
[0078] Intercalation voltage step profile simulation Intercalation voltage profiles were calculated with CP2K v5.1 using the dispersion-corrected (D3) PBE functional and double zeta (triple zeta for bromides) short distances, a molecularly optimized valence basis set, and Goedecker-Teter-Hutter (GTH) pseudopotentials appropriate for the core electrons. The plane wave energy cutoff was set to 1000 Ry, and the Brillouin zone was sampled only at the Γ point. Geometry and cell optimizations converged to a maximum change in atomic positions between steps of 0.0005 au. Other convergence criteria were left at default.
[0079] Li + Intercalation voltage (E int ) can be calculated from a series of energy calculations, assuming negligible entropy contributions, as follows:
number
[0080] The above discussion of the invention has been presented for purposes of illustration and description. The above is not intended to limit the invention to the form or forms disclosed herein. The description of the invention includes one or more embodiments and descriptions of certain variations and modifications, but other variations and modifications may be within the scope of the invention, e.g., within the skill and knowledge of one of ordinary skill in the art after understanding the present disclosure. It is intended to be entitled to include alternative embodiments to the extent permitted, including alternative, interchangeable, and / or equivalent structures, functions, ranges, or steps to those claimed, regardless of whether such alternative, interchangeable, and / or equivalent structures, functions, ranges, or steps are disclosed herein, and without any intention to publicly dedicate them to any claimable subject matter. All references cited herein are incorporated by reference in their entirety.
Claims
1. a composite cathode comprising at least one lithium salt and graphite; An aqueous electrolyte; An anode; 1. A rechargeable lithium ion battery comprising: Rechargeable lithium-ion battery with a capacity of over 200 mAh / g.
2. 2. The rechargeable lithium ion battery of claim 1, wherein an oxidation product of the at least one lithium salt is intercalated within the graphite.
3. 2. The rechargeable lithium-ion battery of claim 1, wherein the composite cathode comprises multiple lithium salts.
4. 10. The rechargeable lithium-ion battery of claim 1, wherein the composite cathode comprises lithium chloride, lithium bromide, lithium iodide, lithium fluoride, and other halogen salts, or combinations thereof.
5. 5. The rechargeable lithium-ion battery of claim 4, wherein the lithium salt comprises a combination of lithium chloride and a lithium salt.
6. 10. The rechargeable lithium-ion battery of claim 1 having an energy density of at least 400 Wh / kg.
7. 10. The rechargeable lithium ion battery of claim 1 having a coulombic efficiency of at least 95%.
8. At least 4 V (Li / Li + 2. The rechargeable lithium-ion battery of claim 1, having a potential of
9. 2. The rechargeable lithium-ion battery of claim 1, wherein the aqueous electrolyte comprises a water-in-two-salt electrolyte (WiBS), a high-concentration organic electrolyte, an all-solid-state ceramic electrolyte, or a combination thereof.
10. The WiBS is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluoro(oxalato)borate (LiDFOB), lithium hexafluoroarsenate (LiAsF 6 ), lithium perchlorate (LiClO 4 ), lithium nitrate (LiNO 3 10. The rechargeable lithium ion battery of claim 9, comprising:
11. 1. A method of making a lithium salt-graphite composite cathode for use in a rechargeable lithium ion battery, comprising compressing a mixture of a lithium salt-graphite composite and a polymer under conditions sufficient to produce a lithium salt-graphite composite cathode, thereby oxidizing the lithium salt and intercalating an oxidation product of the lithium salt within the graphite.
12. 12. The method of claim 11, further comprising the step of mixing a lithium salt with graphite prior to mixing with the polymer and milling the mixture to form the lithium salt-graphite composite material.
13. 13. The method of claim 12, wherein the lithium salt comprises lithium bromide and lithium chloride in a 1:1 molar ratio.
14. 14. The method of claim 13, wherein the mass ratio of the lithium bromide, the lithium chloride, and the graphite is 2:1:
2.
15. 12. The method of claim 11, wherein the polymer comprises poly(vinylidene fluoride) (PTFE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, or a mixture thereof.
16. 12. The method of claim 11, wherein the mass ratio of the lithium salt-graphite composite to the polymer is 95:
5.
17. a composite cathode comprising at least one lithium salt and graphite; wherein the composite cathode is configured such that the lithium salt is oxidized and an oxidation product of the lithium salt is intercalated within the graphite; An aqueous gel electrolyte; an anode comprising a highly fluorinated ether polymer; Includes a rechargeable lithium-ion battery.
18. 18. The rechargeable lithium-ion battery of claim 17 having an energy density of at least 400 Wh / kg.
19. 18. The rechargeable lithium ion battery of claim 17 having a coulombic efficiency of at least 95%.
20. At least 4 V (Li / Li + 18. The rechargeable lithium ion battery of claim 17, having a potential of
21. 18. The rechargeable lithium-ion battery of claim 17, wherein the aqueous gel electrolyte comprises a water-in-two-salt electrolyte (WiBS).
22. The WiBS is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiOTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium difluoro(oxalato)borate (LiDFOB), lithium hexafluoroarsenate (LiAsF 6 ), an asymmetric ammonium salt (Me3EtN.TFSI), N-propyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (pyr13TFSI), or a mixture thereof.
23. 20. The rechargeable lithium ion battery of claim 17, wherein the water-based gel electrolyte further comprises an organic solvent.
24. 24. The rechargeable lithium ion battery of claim 23, wherein the organic solvent comprises trimethyl phosphate, ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), gamma-butyrolactone (gamma-BL), ethyl methyl carbonate, dimethoxyethane, diglycol methyl ether, fluoroethylene carbonate (FEC), or a mixture thereof.
25. 18. The rechargeable lithium ion battery of claim 17, wherein at least a portion of the lithium salt is phase separated from the aqueous gel electrolyte.
Citation Information
Patent Citations
Sea water battery
JP2014212111A
Aqueous rechargeable dual-ion battery
JP2019029077A
Hybrid aqueous secondary battery
JP2019033075A
